Perancangan Penjadwalan Preventive Maintenance Mesin Disamatic Pada Proses Molding Guna Meminimasi Defect Pada Produk Flange 15b di PT. Xyz Menggunakan Metode Perhitungan Mttf dan Mttr - Varyna Ayu Rahmalisa Wibowo; Marina Yustiana Lubis; Yunita Nugrahaini (Jurnal Ilmiah Wahana Pendidikan, 2022)
PT. XYZ is a company engaged in metal casting, aluminum, copper and one type of product that is produced is Flange 15B. Based on historical data on the number of defects in the Flange 15B product. Molding process has the highest percentage of 44% of the total number in producing defective products. The proposed solution to improve the molding process is to provide a preventive maintenance scheduling design for disamatic machines. Solving the problem using the DMAI approach (Define, Measure, Analyze, Improve) and there is a problem, namely the pressure is not appropriate so that the engine thrust is weak caused by a torn membrane and an open blow top valve and then in designing preventive maintenance scheduling researchers use the calculation method MTTF (Mean Time to Failure) and MTTR (Mean Time to Repair). Based on the results of the calculation of the MTTF value, preventive maintenance on disamatic machines has an interval of 21days for membrane replacement and 35 days for repair of blow-up valves from previous damage. The results of the proposed preventive maintenance scheduling design are expected to minimize the number of product defects and improve the problematic process in the Molding process by 70% so that it can increase the existing sigma level value of 3,441 to 3,648.